Use of 4D Printing in Orthodontics: Self-Adjusting Brackets for Dynamic Tooth Movement - Mohammad Khursheed Alam; Mohammad Younis Hajeer; Ebtehal Dhyab M. Alserhani; Talal Olayan Albuhiran; Abdulrhman Atyah Alzhrani; Abdullah Musallam Alsalem; Salman Ahmed Aljudaya; Hind Hani Alruwaili (Journal of Pharmacy and Bioallied Sciences)
Background: 4D printing, an evolution of 3D printing, incorporates time as the fourth dimension to enable shape-changing materials to respond to external stimuli. Its application in orthodontics is a burgeoning field, offering possibilities for self-adjusting brackets that adapt dynamically to the biomechanical requirements of tooth movement. This study evaluates the feasibility and efficacy of 4D-printed self-adjusting brackets in achieving controlled and dynamic orthodontic tooth movement. Materials and Methods: Self-adjusting orthodontic brackets were fabricated using 4D printing technology with shape-memory polymers (SMPs). The brackets were designed to respond to thermal stimuli and were programmed to apply a controlled force of 150–200 g/cm2 for optimal tooth movement. Twenty patients with malocclusions were enrolled, with each receiving self-adjusting brackets on one dental arch and conventional brackets on the opposite arch as a control. The evaluation period spanned six months, with periodic measurements of tooth movement using 3D digital scanning and bite force analysis. Results: The 4D-printed self-adjusting brackets demonstrated a 30% faster rate of tooth movement (mean: 1.5 mm/month) compared to conventional brackets (mean: 1.1 mm/month). Patients reported reduced discomfort, with a pain score of 3.2 ± 0.5 compared to 5.8 ± 0.7 in the control group. The self-adjusting brackets maintained consistent force levels, reducing the need for frequent adjustments by 40%. Conclusion: 4D printing offers a revolutionary approach to orthodontic treatment through self-adjusting brackets, enhancing treatment efficiency and patient comfort. The use of SMPs enables precise and adaptive force application, reducing chairside adjustments and overall treatment duration. Further studies are needed to explore long-term outcomes and cost-effectiveness.